The Influence of Digital Marketing, Product Quality, and Price on Purchase Decisions at Arjuna Coffee by Perlabian - Siti Rahma; Aulia Indra; Yanto Zelibu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the influence of digital marketing, product quality, and price on purchase decisions at Arjuna Cafe Perlabian Labuhanbatu Selatan. This study uses a quantitative approach with a survey method. The population in this study is all Arjuna Cafe consumers, with sampling techniques using accidental sampling methods. Data was collected through questionnaire deployment and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study show that partially digital marketing has a positive and significant effect on purchasing decisions. Product quality also has a positive and significant effect on purchase decisions. In addition, prices have a positive and significant effect on purchasing decisions. Simultaneously, digital marketing, product quality, and price have a significant effect on purchasing decisions at Arjuna Cafe Perlabian Labuhanbatu Selatan. These findings indicate that improving digital marketing strategies, consistency of product quality, and pricing that matches consumer purchasing power can improve purchasing decisions. Therefore, Arjuna Cafe's management needs to optimize these three factors to increase competitiveness and sales volume.